2001
DOI: 10.1136/oem.58.4.239
|View full text |Cite
|
Sign up to set email alerts
|

Cross sectional and longitudinal study on selenium, glutathione peroxidase, smoking, and occupational exposure in coal miners

Abstract: Objectives-To understand the variations of selenium (Se) concentration relative to changes in occupational exposure to coal dust, taking into account age and changes in smoking habits in miners surveyed twice, in 1990 and 1994. To better understand the relation of Se concentration with glutathione peroxidase activities (GSHPx) in these miners. Methods-In 1994, blood samples were obtained from active (n=131) and retired (n=40) miners without coal worker's pneumoconiosis, in whom Se concentration was available a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…SOD activity was also inhibited in all groups examined and a similar response was also found in other studies involving coal mining workers [10,13]. On the other hand, rats exposed sub-chronically to a mine ambience showed SOD and GPx induction at the first week followed by SOD inhibition at the fourth week of exposure [22].…”
Section: Before the Antioxidant Interventionsupporting
confidence: 65%
See 4 more Smart Citations
“…SOD activity was also inhibited in all groups examined and a similar response was also found in other studies involving coal mining workers [10,13]. On the other hand, rats exposed sub-chronically to a mine ambience showed SOD and GPx induction at the first week followed by SOD inhibition at the fourth week of exposure [22].…”
Section: Before the Antioxidant Interventionsupporting
confidence: 65%
“…The first finding regarding coal extraction, was a systemic OS present in the blood or workers directly or indirectly exposed to PM emissions related to coal mining [1], in general accordance to the related literature [10,13,16]. More importantly, they also revealed that people living in the vicinity (ca.…”
Section: After the Antioxidant Interventionsupporting
confidence: 60%
See 3 more Smart Citations